Possible glass-like random singlet magnetic state in 1T-TaS2. (21st October 2019) - Pal, Sudip; Kumar, Kranti; Sharma, Rohit; Banerjee, A; Roy, S B; Park, Je-Geun; Nigam, A K; Cheong, Sang-Wook
Abstract: Two-dimensional layered transition-metal-dichalcogenide compound 1T-TaS2 shows the rare coexistence of charge density wave (CDW) and electron correlation driven Mott transition. In addition, atomic-cluster spins on the triangular lattice of the CDW state of 1T-TaS2 give rise to the possibility of the exotic spin-singlet state in which quantum fluctuations of spins are strong enough to prevent any long range magnetic ordering down to the temperature absolute zero (0 K). We present here the evidences of a glass-like random singlet magnetic state in 1T-TaS2 at low temperatures through a study of temperature and time dependence of magnetization. Comparing the experimental results with a representative canonical spin-glass system Au(1.8%Mn), we show that this glass-like state is distinctly different from the well established canonical spin-glass state.